Hubungan antara Daya Analitis dan Daya Kreativitas Terhadap Hasil Belajar Sub Keilmuan Informatika pada Siswa Jurusan Multimedia, TKJ dan RPL (Studi Kasus: SMK Negeri Se-Bali) - Ary Widayanti, Putu; Sugihartini, Nyoman; Windu Antara Kesiman, Made; Seri Wahyuni, Dessy (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This study aimed to (1) determine the relationship between the analytical ability of the sub- science informatics learning outcomes for students majoring in Multimedia, TKJ and RPL in SMK in Bali, (2) determine the relationship between the creativity ability of the sub-science informatics learning outcomes for students majoring in Multimedia, TKJ and RPL in SMK in Bali, (3) determine the relationship between the analytical ability and creativity ability to the learning outcomes of sub science informatics student majoring in Multimedia, TKJ and RPL SMK in Bali.This type of research is an ex post facto research, which consists of two independent variables and the dependent variable. The population is using the region's population. The sample of this study was representative of a population of 262 students. Data collection used questionnaires. Trial conducted at 90 research instruments students. Once the questionnaire is valid, then the questionnaire distributed in eight schools, then the data were analyzed using parametric statistical test with the prerequisite of normality, linearity, and multicollinearity.The result of the research were (1) there is no positive and significant relationship between the analytical ability of the learning outcomes in sub- science informatics SMK Bali as well to Multimedia majors, TKJ and RPL, (2) there is no positive and significant relationship between creativity ability and the learning outcomes of sub SMK scientific informatics in Bali for majors as Multimedia and RPL, (3) there is a positive relationship and significantly between the power of creativity to the learning outcomes of sub science informatics at SMK Bali as a contribution to the majors TKJ with a contribution 11.6%, (4) there is no positive and significant relationship jointly between the analytical ability and creativity ability to the learning outcomes of sub scientific informatics for Multimedia majors and RPL, (5) there is a positive and significant relationship jointly between the analytical ability and creativity ability to the learning outcomes of sub science informatics SMK in Bali for a major TKJ contribution of 19.3 %.